Environmental niche overlap in sibling planktonic species Calanus finmarchicus and C. glacialis in Arctic fjords. Issue 12 (8th December 2022) - Weydmann‐Zwolicka, Agata; Cottier, Finlo; Berge, Jørgen; Majaneva, Sanna; Kukliński, Piotr; Zwolicki, Adrian
Abstract: Knowledge of environmental preferences of the key planktonic species, such as Calanus copepods in the Arctic, is crucial to understand ecosystem function and its future under climate change. Here, we assessed the environmental conditions influencing the development stages of Atlantic Calanus finmarchicus and Arctic Calanus glacialis, and we quantified the extent to which their niches overlap by incorporating multiple environmental data. We based our analysis on a 3‐year seasonal collection of zooplankton by sediment traps, located on moorings in two contrasting Svalbard fjords: the Arctic Rijpfjorden and the Atlantic‐influenced Kongsfjorden. Despite large differences in water temperature between the fjords, local realized ecological niches of the sibling Calanus species overlapped almost perfectly. The exception was the earliest copepodites of C. glacialis in Rijpfjorden, which probably utilized the local ice algal bloom in spring. However, during periods with no sea ice, like in Kongsfjorden, the siblings of both Calanus species showed high synchronization in the population structure. Interestingly, differences in temperature preferences of C. finmarchicus and C. glacialis were much higher between the studied fjords than between the species. Our analysis confirmed the high plasticity of Calanus copepods and their abilities to adapt to highly variable environmental settings, not only on an interannual basis but also in a climate warming context, indicating some resilience in the Calanus community. Abstract : We assessed environmental conditions influencing the development stages of Atlantic Calanus finmarchicus and Arctic Calanus glacialis, and we quantified the extent to which their niches overlap based on a three‐year seasonal collection of zooplankton by sediment traps, located on moorings in two contrasting Svalbard fjords: the Arctic Rijpfjorden and the Atlantic‐influenced Kongsfjorden. Despite large differences in water temperature between the fjords, local realized ecological niches of the sibling Calanus species overlapped almost perfectly. Our analysis confirmed the high plasticity of Calanus copepods and their abilities to adapt to highly variable environmental settings, not only on an interannual basis but also in a climate warming context, indicating some resilience in the Calanus community.